2021
DOI: 10.21203/rs.3.rs-985205/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of forage proportion and ensiling periods on physical characteristics and qualities of Panicum maximum (Ntchisi) and Stylosanthes guianensis silage

Abstract: This study was carried out to evaluate the effect of proportion of grass-legume mixtures and ensiling periods on the physical characteristics and qualities of Panicum maximum and Stylosanthes guainensis silage. The experiment was laid in a 2×3 factorial arrangement which comprised of two (2) forage proportions (100% and 50%:50%) and three (3) ensiling periods (30, 60 and 90 days). Results showed that there was only significant (p<0.05) different on pH as affected by ensiling periods whereby the pH values de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…As suggested in the results, silages made of 100% grasses (Treatment 1: Brachiaria mulato and Panicum coloratum) presented relatively greater percentages of neutral detergent bers (%), acid detergent bers (%), pH, total fermentation losses (g) and dry matter (DM%) than did mixtures of Brachiaria mulato (70%) + Desmodium distrortum (30%) and Panicum coloratum (70%) + Desmodium distortum (30%). In previous studies, NDF was found to range from 53.7-70.6%, while signi cant variations among the treatments were found for NDF and ADF in mixed silages (grass * legumes); in contrast, the sole panicum maximum silage contained 59.67% NDF and 33.83% ADF (Okukenu et al, 2021). This nding indicates a certain similarity with ndings from the current studies.…”
Section: Discussionsupporting
confidence: 86%
“…As suggested in the results, silages made of 100% grasses (Treatment 1: Brachiaria mulato and Panicum coloratum) presented relatively greater percentages of neutral detergent bers (%), acid detergent bers (%), pH, total fermentation losses (g) and dry matter (DM%) than did mixtures of Brachiaria mulato (70%) + Desmodium distrortum (30%) and Panicum coloratum (70%) + Desmodium distortum (30%). In previous studies, NDF was found to range from 53.7-70.6%, while signi cant variations among the treatments were found for NDF and ADF in mixed silages (grass * legumes); in contrast, the sole panicum maximum silage contained 59.67% NDF and 33.83% ADF (Okukenu et al, 2021). This nding indicates a certain similarity with ndings from the current studies.…”
Section: Discussionsupporting
confidence: 86%